1995
DOI: 10.1159/000139275
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Leukotriene Production by FK506 in Rat Basophilic Leukemia-1 Cells

Abstract: We investigated the inhibitory action of FK506 (0.0005-5 µg/ml) on the metabolism of arachidonate 5-lipoxygenase in rat basophilic leukemia-1 cells. Cells were stimulated with A23187 (10-5 mol/l) for 15 min in the absence or presence of various concentrations of FK506. Arachidonate 5-lipoxygenase metabolites, peptide leukotrienes (LTs), leukotriene B4 (LTB4) and 5-hydroxyeicosatetraenoic acid (5-HETE) were measured by high-performance liquid chromatography. FK506 inhibited A231… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Furthermore, limited effects of FK506 on AA release and cPLA 2 activity reported in the present study are in agreement with previously published results of studies performed on cell types other than astrocytes (69,70). …”
Section: +supporting
confidence: 94%
“…Furthermore, limited effects of FK506 on AA release and cPLA 2 activity reported in the present study are in agreement with previously published results of studies performed on cell types other than astrocytes (69,70). …”
Section: +supporting
confidence: 94%
“…FK-506 exerts neuroprotection through calcineurin-independent mechanisms such as lowered production of leukotrienes and arachidonic acid [77,78] and heat shock protein upregulation [79,80]. Studies have shown that FK-506 reduces lipid peroxidation, COX-2 activity, and caspase-3 activation [81,82].…”
Section: Fk-506mentioning
confidence: 99%
“…FK506 could also exert calcineurin-independent actions such as leukotriene and arachidonic acid inhibition [72][73][74] or heat shock proteins up-regulation [75,76]. FK506 could also exert calcineurin-independent actions such as leukotriene and arachidonic acid inhibition [72][73][74] or heat shock proteins up-regulation [75,76].…”
Section: Fk506mentioning
confidence: 99%